Highlights of the Annual Meeting of the Association for European Paediatric and Congenital Cardiology. (September 2013) - Konta, Laura; Hayes, Nicholas; Qureshi, Shakeel A
The 47th annual meeting of the Association for European Paediatric and Congenital Cardiology was held on 22–25th May 2013 in London, UK. This is one of the largest scientific meetings in Europe within the field of congenital cardiac disease and was held in association with the Japanese Society of Pediatric Cardiology and Cardiac Surgery, and Asia Pacific Pediatric Cardiology Society. There were 900 submitted abstracts and over 1000 delegates from 57 countries attended. We have summarized some of the highlights of the meeting below.